PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT BANK CENTRAL ASIA, TBK. KCU KEBAYORAN BARU - Zulindra, Yumna Puspa Sari; Ajimat, Ajimat (CV. Pena Persada, 2019)
The purpose of this study was to find out the motivation of employees of PT Bank Central Asia, Tbk. KCU Kebayoran Baru, to find out the job satisfaction of employees of PT Bank Central Asia, Tbk. KCU Kebayoran Baru, to determine the performance of employees at PT Bank Central Asia, Tbk. KCU Kebayoran Baru, to find out the influence of motivation on employee performance at PT Bank Central Asia, Tbk. KCU Kebayoran Baru, to determine the effect of job satisfaction on employee performance at PT Bank Central Asia, Tbk. KCU Kebayoran Baru, to determine the effect of motivation and job satisfaction on employee performance at PT Bank Central Asia, Tbk. KCU Kebayoran Baru. The research method used in this study is quantitative associative methods and data collection with questionnaire techniques. The method of determining the number of samples with saturated sample technique obtained a sample of 65 employees. Data analysis method with validity test, reliability test, classic assumption test, multiple linear regression analysis, multiple correlation coefficient test, analysis of determination coefficient, hypothesis test. The results showed that the multiple correlation coefficient = 0.677 means that motivation and job satisfaction have a strong influence on employee performance. In multiple linear regression at Y = 6.764 + 0.266X1 + 0.656X2. The coefficient of determination is 67.7% which shows the contribution of motivation and job satisfaction to employee performance by 67.7% while the remaining 32.3% is influenced by other variables not examined. The significance test results obtained the value that t count> t table or 6,800> 1,997 on the motivation variable and 10,632> 1,997 on the variable job satisfaction then H1 is accepted and Ho is rejected, meaning there is a significant influence between motivation and job satisfaction on employee performance at PT Bank Central Asia, Tbk. KCU Kebayoran Baru.